THE RESULTS OF THE USE OF CLOUD TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF PEDAGOGICAL UNIVERSITIES IN A PANDEMIC - Sobchenko, Tetiana; Dotsenko, Svitlana; Tkachova, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The research relevance ties with the necessity to form future teachers’ digital competence under forced blended learning conditions due to COVID-19 preventive quarantine measures implementing. The purpose of the article is to reveal the content and analyze the results of the study on the experience in cloud technologies usage while teaching pedagogical courses to students in a modern pedagogical higher education institution. The methods are: theoretical analysis of the cloud technologies usage in higher education institutions, documentation analysis in the European Higher Education Area, information collection, questionnaires for students and lecturers, observation, evaluation, systematization of the results. The results are: the experience in cloud technologies usage while teaching pedagogical courses to future teachers is determined; issues with the information and communication technologies usage are identified: constant access to the network, poor service, lack of equipment. It has been clarified that students gained an enough experience in cloud technologies usage before the quarantine same as during it, identified the factors that contributed to it (inclusion in distance learning, studying the course “Digital Technologies”, testing of cloud services and technologies). It has been established that the lecturers used to have small experience in cloud technologies usage before the quarantine because there was no special necessity, but during it, these indicators have changed (forced distance learning and the conditions for its implementation contributed to the rapid capture of cloud services, attending courses, testing the experience in cloud technologies usage). The most popular cloud technologies are Classroom, Zoom, Meet, Moodle have been lined out.